SAPA, science and society: A debacle revisited - Long, Wahbie (PINS-Psychology in Society, 2025)
Little is known about the first national association to be established for psychologists in South Africa: the South African Psychological Association (SAPA). While it is commonly assumed that Anglophone psychologists were politically enlightened in comparison with their Afrikaner counterparts, this paper attempts to illuminate the complexities of SAPA’s intellectual project. Offering a critical discourse analysis of eight presidential and opening addresses delivered at national congresses between 1950 and 1962, the paper identifies among SAPA’s Afrikaner presidents a preoccupation with a socially relevant psychology, enunciated in the form of a professionalist discourse that encouraged public service yet bore no trace of Christian-National influence. Among English-speaking psychologists, by contrast, social responsiveness was less of a priority in a discourse of disciplinarity concerned with fundamental debates in the field. It is suggested that these divergent conceptions regarding the role of psychology in society presaged the SAPA split of 1962 and provide, also, an important historical perspective from which to view a contemporary struggle within the discipline.